REDTONE INTERNATIONAL BERHAD: A THEORETICAL STUDY - Johar; MGM; Yajid, Mohd Shukri Ab; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this case study is to examine and understand the Malaysian tier-2 telco industry with special focus on Redtone International Berhad and its position in the market place. The case analysis includes application of models such as External / Internal Evaluation Matrix, Porter’s Model, SPACE Matrix and Ansoff’s Matrix. The methodology adopted for this case study is by industry observation through mass media, reference to company annual reports, collection of industry analysis, articles and information in the internet and referring to the company personne (Abdullah, Abdullah, & Salleh, 2017).